The Contribution of Napoleon Bonaparte to Egyptology - Jock Matthew Agai; M. Yoserizal Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Egyptology is a collection of many disciplines including history, arts, mathematics and sciences. While some scholars argued that the formal study of Egypt can be dated back to the pre-Greco Roman period, others objected to this notion and they proposed that Egyptology officially started from the 18th century after Napoleon’s invasion of Egypt. Not all people applauded Napoleon as the father of Egyptology after his exploitation and exploration of Egypt. Many Afrocentric scholars blamed Napoleon for dissociating the Egyptian civilization from other Africans while a number of Eurocentric scholars emphasized only the legendaries or positive contribution of Napoleon. This paper is limited to not making conclusions about the position of both Afrocentric and Eurocentric scholars on Napoleon. The paper is an emphasis on Napoleon’s contribution to Egyptology and to scientific studies. Using the background of his biographical engagements with other scientists, I argued that there are certain administrative skills endowed upon Napoleon that worth commendation for both Africans and non-Africans.